Sistem Penjaminan Mutu Pendidikan Dalam Meningkatkan Mutu Pendidikan Sekolah Dasar Di Kecamatan Gajah Mungkur Kota Semarang - Haryono Haryono; Budiyono Budiyono; Istyarini Istyarini; Wardi Wardi; Apri Ardiantoro (Universitas Negeri Semarang, 2019)
Quality assurance is a series of processes and related systems to collect, analyze, and report data on the performance and quality of educators and education personnel, programs and institutions. The quality assurance process identifies aspects of achievement and priority for improvement, provides data as a basis for planning and decision making and helps build a culture of continuous improvement. The achievement of the quality of education for primary and secondary education in Indonesia is assessed based on the eight National Education Standards of the BSNP. The regional autonomy policy has an impact on the management of education in the region. Efforts to standardize quality must be the focus of attention in an effort to maintain the quality of education nationally. The quality assurance and improvement system of primary and secondary education in Indonesia operates within an education management and government system that delegates most of the responsibility for implementation to provinces, districts, foundations and schools/madrasahs. Achievement of education quality for primary and secondary education is assessed based on the eight National Education Standards from the BSNP. the system of guaranteeing and improving the quality of education in elementary school education in Gajahmungkur District, Semarang City is related to three main aspects, namely: (1) Studying the concept of Education Quality Assurance, (2) Development of an effective education quality information system for management, decision making in assurance and improving the quality of education, and (3) Continuous Education Quality Assurance System through School Self Evaluation (EDS) to step into the education quality assurance process.